Reflections on the history and legacy of scientific racism in South African palaeoanthropology and beyond - Ackermann, Rebecca, Rogers (My University, 2018)
The history of scientific discovery is overwhelmingly told as a narrative of the lives and discoveries of a series of remarkable white men. Christa Kuljian’s real triumph in this book is that she reframes the narrative of palaeoanthropological discovery in South Africa as a tale of flawed men who succeed – through some combination of luck, skill, personality and perseverance – literally and figuratively on the backs of black bodies. That she tells this story with limited cynicism and anger is a testament to the author. This book takes a rich, personal, archivally-intensive and interview-based look at the history of palaeoanthropology that is uncommon in our field, focussing on a region of the world where the global context of racism and the eugenics movement in the 20th century was further compounded by state-sanctioned apartheid. It is a timely tale of racism and misogyny and how they shape scientists, the scientific enterprise, and narratives of human origins and evolution. Although a large portion of this book is historical, it brings the reader right up to the present, and contains themes that remain relevant today, in the age of #BlackLivesMatter, #MeToo, and other pertinent movements, and affect our field more generally. In this review, I will first provide a very brief summary of the book. I will then highlight what I believe are the book’s most salient themes that are relevant to biological anthropology today: racism in science, intersectionality, and the invalid (but still prevalent) idea that scientists and their work can be separated. Finally, I will consider current practice in palaeoanthropology, as well as various reviews of the book, in order to reflect on these issues.
Supplemental Materials: https://osf.io/ftwc7/
Keywords: Scientific racism; palaeoanthropology; Africa